Synthesis of zeolite from fly ash and its adsorption of phosphorus in wastewater - Zhang Kecheng (De Gruyter, 2021)
Using synthetic zeolite from fly ash to treat high concentration phosphorus wastewater does not only improve the utilization of fly ash as solid waste but also reduce the environmental pressure caused by eutrophication. A synthetic zeolite was prepared from coal fly ash by one-step hydrothermal synthesis and applied for phosphorus adsorption from industrial wastewater (∼8,000 mg-P/L), and its adsorption characteristics and performance were studied. The results indicated that the product was a well-crystallized Na-P1 zeolite with typical morphology of plate- and rod-shaped crystals. Compared with the original fly ash, the specific surface area and average pore volume of the synthetic zeolite were nine and six times larger than the fly ash, reaching 43.817 m2/g and 0.122 cm3/g. The results from phosphorus adsorption onto the synthetic zeolite showed that the synthetic zeolite had good phosphorus adsorption properties. The adsorption process highly conformed to the pseudo-second-order kinetic model with the regression coefficient R 2 of 0.998. Phosphorus adsorption on the synthetic zeolite was fitted to the Langmuir monolayer adsorption model, and the regression coefficient R 2 was 0.989. The maximum phosphorus adsorption capacity was 84.4 mg-P/g-zeolite.